PENGEMBANGAN MODUL BERBASIS PENDEKATAN SAINTIFIK DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA MATERI DUNIA TUMBUHAN (PLANTAE) KELAS X SMA - Dewi Suherni; Arnentis Arnentis; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The world of plants (Plantae) is one of the subjects Biology class X is quite difficult. Since the number of division or classification of the plant world (Plantae). To be able to classify the necessary knowledge of general characteristics, structure and function of the body, the way of life and habitats as well as the mode of reproduction of these plants that were studied in detail. The purpose of this research is to increase understanding and knowledge of students about the world of plants (Plantae). This research was conducted at the Laboratory of Biology Department of the University of Riau PMIPA FKIP and SMAN 8 Pekanbaru in March to July 2017. The research is a research development by using ADDIE model of integration to the stage of development. There are 5 learning developed. Instruments of data collection in this study is the assessment sheet/validation module, and questionnaire responses of learners. After module developed, validated by 4 validator then the tests I in the 4th semester 15 students of biology education FKIP UR, and a second trial on 20 students of Class XI SMAN 8 Pekanbaru. The tests showed the average score feasibility aspects of the content of 5 learning developed valid category is 3,91, the average score 3,99 categories designing aspect is valid, and the mean score of the pedagogic aspect is 3,97 valid category. The mean overall score of the fifth aspect is 3.95 is valid category. I trial results showed the average score 4.05 with good category. II trial results showed a mean score of 3.83 in good categories. The results of the analysis of the answers to the first trial showed a mean value of 81.8 in good categories. module Scientific Approach Based on Material World of Plants (Plantae) can increase the understanding and knowledge about the world of plants (Plantae) and can increase critical thinking ability of learners.Key Words: Development, module, Scientific Approach, Critical Thinking, World of Plants (Plantae)